Characteristics of the Salivary Microbiota in Patients With Various Digestive Tract Cancers - Kageyama, Shinya; Takeshita, Toru; Takeuchi, Kenji; Asakawa, Mikari; Matsumi, Rie; Furuta, Michiko; Shibata, Yukie; Nagai, Kiyoshi; Ikebe, Masahiko; Morita, Masaru; Masuda, Muneyuki; Toh, Yasushi; et al. (Frontiers in Microbiology, 2019)
The salivary microbiota is constantly swallowed and delivered to the digestive tract. These bacteria may be associated with gastrointestinal diseases. This case-control study examined the salivary microbiota in patients with digestive tract cancer (DTC) and evaluated their differential distribution based on the cancer sites. We collected saliva samples from 59 patients with cancer in any part of the digestive tract (tongue/pharynx, esophagus, stomach, and large intestine) and from 118 age- and sex-matched control subjects. There was no significant difference in periodontal status between DTC patients and control subjects (P = 0.72). We examined the bacterial diversity and composition in saliva by 16S ribosomal RNA gene sequencing. Salivary bacterial diversity in DTC patients was significantly higher than that in control subjects (number of operational taxonomic units [OTUs], P = 0.02; Shannon index, P < 0.01; Chao1, P = 0.04). Eleven differentially abundant OTUs in DTC patients were identified using the linear discriminant analysis effect size (LEfSe) method. Based on the cancer sites, the diversity of salivary bacteria was especially higher in tongue/pharyngeal or esophageal cancer patients than in control subjects. Among the 11 differentially abundant OTUs in DTC patients, an OTU corresponding to Porphyromonas gingivalis was more abundant in the saliva of all groups of DTC patients compared to that in control subjects, and an OTU corresponding to Corynebacterium species was more abundant in all groups other than gastric cancer patients (P < 0.01). In addition, the relative abundances of OTUs corresponding to Fusobacterium nucleatum, Streptococcus parasanguinis II, and Neisseria species were significantly higher in tongue/pharyngeal cancer patients compared to their abundances in control subjects (P < 0.01). The relative abundance of an OTU corresponding to the Neisseria species was also significantly higher in gastric cancer patients and that of an OTU corresponding to Actinomyces odontolyticus was significantly higher in colorectal cancer patients (P < 0.01). These results suggest that the salivary microbiota might be associated with various digestive tract cancers.